2006
DOI: 10.2337/diacare.29.04.06.dc05-2011
|View full text |Cite
|
Sign up to set email alerts
|

Adult Treatment Panel III 2001 but Not International Diabetes Federation 2005 Criteria of the Metabolic Syndrome Predict Clinical Cardiovascular Events in Subjects Who Underwent Coronary Angiography

Abstract: OBJECTIVE -The International Diabetes Federation (IDF) has recently established a worldwide consensus definition of the metabolic syndrome. No prospective data are available on the cardiovascular risk associated with this new metabolic syndrome definition. RESEARCH DESIGN AND METHODS-In a prospective study of 750 coronary patients, we recorded vascular events over 4 years.RESULTS -From our patients, 37.3% (n ϭ 280) had the metabolic syndrome according to the Adult Treatment Panel III (ATPIII) definition and 45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
73
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(82 citation statements)
references
References 27 publications
6
73
0
3
Order By: Relevance
“…OB: central obesity analysis. These findings are supported by a previous study revealing that waist circumference was not significantly predictive of vascular events after adjustment for the cardiovascular risk factors [25]. It is apparent that central obesity including visceral and subcutaneous fat defined by waist circumference, a surrogate marker of visceral obesity, is a significant independent predictor of insulin resistance, impaired glucose tolerance, hypertension and dyslipidemia seen in metabolic syndrome [26].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…OB: central obesity analysis. These findings are supported by a previous study revealing that waist circumference was not significantly predictive of vascular events after adjustment for the cardiovascular risk factors [25]. It is apparent that central obesity including visceral and subcutaneous fat defined by waist circumference, a surrogate marker of visceral obesity, is a significant independent predictor of insulin resistance, impaired glucose tolerance, hypertension and dyslipidemia seen in metabolic syndrome [26].…”
Section: Discussionsupporting
confidence: 79%
“…Therefore, the indispensability of central obesity of this new definition may be a cause of the reduced predictive power of carotid atherosclerosis. These findings are supported by recent several studies which revealed the lower predictive power of the IDF definition for CVD than NCEP-ATP III definition, and suggested that one cause of low predictive power for CVD was derived from the indispensability of the waist circumference component [25,32]. When central obesity was one of the components of metabolic syndrome, carotid IMT increased along with the increase in the number of the components of metabolic syndrome.…”
Section: Discussionsupporting
confidence: 76%
“…In one prospective cohort study of 3589 British women free of coronary heart disease at baseline, both the IDF and NCEP definitions were similarly associated with coronary heart disease [19]. However, one prospective study of 20,789 men showed that the NCEP definition is more predictive of CVD mortality than the IDF definition [20], and another prospective study of 750 patients referred to coronary angiography reported that the NCEP definition significantly predicted cardiovascular events but, the IDF definition did not [21]. Further prospective research need to be conducted in order to clarify the predictive ability of the IDF and NCEP definitions for the development of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Nesse caso, a valorização da obesidade central pela IDF como parâmetro-diagnóstico, compreendendo valores de referência reduzidos para cintura abdominal comparados ao NCEP-ATPIII, parece justificar o aumento da prevalência da SM ora evidenciado 28 . No entanto, não necessariamente correspondendo maior efeito preditivo de complicações cardiovasculares, conforme demonstrado por Saely et al 33 . Além disso, a equivalência de padrões antropométricos proposta para populações distintas, vem sendo indicada como possível fator causador de viés nestas análi-ses 35 .…”
unclassified